2010
DOI: 10.1253/circj.cj-09-1019
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-43 Redistribution and Gap Junction Activation During Forced Restraint Protects Against Sudden Arrhythmic Death in Rats

Abstract: Background: Connexin-43 (Cx43) expression is reduced or redistributed in heart disease. Restraint or other emotional stressors might cause sudden death in persons with such diseases, but the mechanism of death and its connection to Cx43 during restraint remain unknown. Whether Cx43 distribution or gap junction (GJ) function during restraint is involved in sudden arrhythmic death in rats is addressed in this study. Methods and Results:Male Sprague -Dawley rats underwent immobilization (IMO), and individual elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Previously, we demonstrated that IMO induced arrhythmic death when coupled with the GJ inhibition that frequently results from heart diseases. 9,10) This study has provided additional support for the hypothesis on the role of cardiogenic death in restraint.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previously, we demonstrated that IMO induced arrhythmic death when coupled with the GJ inhibition that frequently results from heart diseases. 9,10) This study has provided additional support for the hypothesis on the role of cardiogenic death in restraint.…”
Section: Discussionsupporting
confidence: 58%
“…8) We also showed that whereas IMO induced enhanced gap-junction (GJ) coupling through α-AR, it triggered lethal ventricular arrhythmias when GJ was inhibited. 9,10) Stress (takotsubo) cardiomyopathy is typically induced by psychological stress in postmenopausal women, and is characterized by apical myocardial akinesis and preserved basal movement, which is reflected by a takotsubo (Japanese octopus trap)-like ventriculogram.…”
Section: -3)mentioning
confidence: 99%
“…The physical restraint induced SCD in young males without structural heart disease [41]. Rats underwent immobilization showed the increased premature ventricular contractions [42]. Furthermore, SCD in individuals with underlying cardiac disease can be caused by arrhythmic episodes precipitated by emotional stresses [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of gap junctions appear at the intercalated discs and to a lesser extent along the lateral membranes of the heart cells [51]. The disturbances in Cx43 expression and distribution [51], including the enhanced Cx43 immunofluorescence at intercalated discs [42] were used to evaluate the gap junction remodeling. Immobilization stress induced the enhanced Cx43 immunofluorescence at intercalated discs, in association with gap junction intercellular communication activation in male Sprague -Dawley rats [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation